2016
DOI: 10.1063/1.4954064
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the absorption spectrum and first hyperpolarizability of keto-enol tautomeric forms of anil derivatives: A Monte Carlo/quantum mechanics study

Abstract: Theoretical results for the absorption spectrum and electric properties of the enol and keto tautomeric forms of anil derivatives in the gas-phase and in solution are presented. The electronic properties in chloroform, acetonitrile, methanol, and water were determined by carrying out sequential Monte Carlo simulations and quantum mechanics calculations based on the time dependent density functional theory and on the second-order Møller-Plesset perturbation theory method. The results illustrate the role played … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Numerous reports refer to the solvent polarity as the main factor influencing the keto/enol equilibrium . The strong solvation effect is considered as a main cause of the dominance of the keto form in polar solvents, while in nonpolar solvents the tautomeric equilibrium is usually shifted toward formation of enol forms, most likely due to the formation of internal hydrogen bonds. ,, On the other hand, studies on some specific Schiff bases revealed an opposite solvent-dependent effect taking place in a range of polar and nonpolar solvents . The present work aimed to determine the influence of polar and nonpolar solvents on the enol/keto equilibrium, using solvents with different electric polarizabilities.…”
Section: Introductionmentioning
confidence: 95%
“…Numerous reports refer to the solvent polarity as the main factor influencing the keto/enol equilibrium . The strong solvation effect is considered as a main cause of the dominance of the keto form in polar solvents, while in nonpolar solvents the tautomeric equilibrium is usually shifted toward formation of enol forms, most likely due to the formation of internal hydrogen bonds. ,, On the other hand, studies on some specific Schiff bases revealed an opposite solvent-dependent effect taking place in a range of polar and nonpolar solvents . The present work aimed to determine the influence of polar and nonpolar solvents on the enol/keto equilibrium, using solvents with different electric polarizabilities.…”
Section: Introductionmentioning
confidence: 95%